Three TERT genes in Nicotiana tabacum - Sýkorová, Eva; Fulnečková, Jana; Mokroš, Petr; Fajkus, Jiří; Fojtová, Miloslava; Peška, Vratislav (Chromosome research, 2012)
Telomerase is essential for proper functioning of telomeres in eukaryotes. We cloned and characterised genes for the protein subunit of telomerase (TERT) in the allotetraploid Nicotiana tabacum (tobacco) and its diploid progenitor species Nicotiana sylvestris and Nicotiana tomentosiformis with the aim of determining if allopolyploidy (hybridisation and genome duplication) influences TERT activity and divergence. Two of the three sequence variants present in the tobacco genome (NtTERT-C/s and NtTERT-D) revealed similarity to two sequence variants found in N. sylvestris and another variant (NtTERT-C/t) was similar to TERT of N. tomentosiformis. Variants of N. sylvestris origin showed less similarity to each other (80.5 % in the genomic region; 90.1 % in the coding sequence) than that between the NtTERT-C/s and NtTERT-C/t variants (93.6 and 97.2 %, respectively). The NtTERT-D variant was truncated at the 5' end, and indels indicated that it was a pseudogene. All tobacco variants were transcribed and alternatively spliced sequences were detected. Analysis of gene arrangements uncovered a novel exon in the N-terminal domain of TERT variants, a feature that is likely to be commonly found in Solanaceae species. In addition, species-specific duplications were observed within exon 5. The putative function, copy number and evolutionary origin of these NtTERT sequence variants are discussed.
Keywords: genetická transkripce; Nicotiana; molekulární evoluce; sekvenční seřazení; alternativní sestřih; exony; sekvence nukleotidů; telomerasa; repetitivní sekvence nukleových kyselin; genetické lokusy; Molecular Sequence Data; Evolution, Molecular; Transcription, Genetic; molekulární sekvence - údaje; Telomerase; Exons; Alternative Splicing; Genome, Plant; izoformy RNA; Gene Order; Amino Acid Sequence; Repetitive Sequences, Nucleic Acid; Base Sequence; pořadí genů; tabák; Sequence Alignment; Introns; Gene Rearrangement; genová přestavba; pseudogeny; RNA Isoforms; genom rostlinný; introny; Pseudogenes; Genetic Loci; sekvence aminokyselin